A Phenomenological Study Exploring Student Nurses’ Experiences of Grief. - Tutcher, Hannah (2011)
Nurses’ experience of grief is an area that is poorly researched within the nursing literature. This gap in knowledge is particularly prominent with regards to student nurses’ experiences. This research was carried out in order to explore student nurses experiences of grief whilst caring for dying patients on clinical placements. A hermeneutic phenomenological approach was deemed the most appropriate methodology to use in order to conduct the research. Ethical approval was gained by the University of Nottingham Medical School Ethics Committee in July 2010. Data was generated through unstructured interviews with 8 student nurses who had experienced grief whilst caring for dying patients. Participants were asked, ‘tell me about your experiences of grief whilst caring for dying patients whilst on clinical placement’. Data analysis, guided by the work of Heidegger (1962), Van Manen (1990) and Greatrex- White (2007), uncovered 3 themes: grief processes, nursing and nurses education and future possibilities. These findings bridge the gap in the knowledge of student nurses’ experiences of grief. Findings are discussed in relation to the wider literature on the topic. A greater understanding of the phenomenon has enabled recommendations to be made for ways in which the experience can be improved for student nurses, an example of this is peer support counselling sessions. It has also been recommended that larger-scale research should adopt a similar methodology to further consider the grief experiences of student nurses. A reflection on the research process has been provided, acknowledging that it would be inappropriate to make generalisations about all student nurses’ grief experiences. However, I believe that this study makes a valuable contribution to the sum of knowledge in the subject area.